Expression of large plasmids in the endosymbiotic form of Rhizobium leguminosarum. - Krol, A J (1980)
Isolated plasmid DNA from Rhizobium leguminosarum was hybridised with cellular RNA from broth-cultured bacteria and endosymbiotic bacteroids. From these hybridisation, experiments it is concluded that plasmid genes are strongly expressed in bacteroids and only weakly or not at all in bacteria. From the hybridisation of plasmid DNA with the cloned structural nif genes of Klebsiella pneumoniae it is shown that at least part of the nif genes are located on a plasmid.